Effectiveness of Predict – Observe – Explain Model in Improving Physics concepts and Performance Skills among Al- Isra University Students - Al- Muhtaseb, Sumaya (Jordan Journal of Educational Sciences, 2008)
This study investigated the effectiveness of Predict – Observe – Explain (POEs) model in improving physics concepts and performance skills among Al- Isra University Students. The study used quasi experimental design to answer the research questions, and chose An intended sample consisted of 36 pharmacy students distributed equally into two groups: experimental group studied by POEs model and control group studied by traditional laboratory method (Kook Book Like). Worksheets were developed according to POEs. Data were collected using Physics concept test and performance skills observation checklist. T – test was used to measure the differences between the tow groups and revealed that there were significant difference between the two methods in acquiring physics concepts and performance skills in favor of POEs group. The study recommended that POEs model should be adopted in university physics laboratory and the instructors should be trained to develop university teaching methods